Phytochemical contents, antioxidant and antibacterial activity of the ethanolic extracts of Centella asiatica(L.) Urb.leaf and stem - Polash, Shakil Ahmed; Saha, Tanushree; Hossain, Md Sharif; Sarker, Satya Ranjan (Jahangirnagar University Journal of Biological Sciences, 2017)
Abstract not available Jahangirnagar University J. Biol. Sci. 6(1): 51-57, 2017 (June)